Design and analysis of concentric tube heat exchanger using entropy generation minimisation. (2014) - Pitchandi, K.
In a heat exchanger, the amount of heat that is transferred at relatively high temperature is of greater importance than heat balance. This would ensure the conservation of exergy. The entropy generation is the only quantity that quantifies the loss in the exergy. In the present study the entropy generation in concentric tube heat exchanger, and the effect of geometry and working parameters on it, are discussed. A mathematical model for the concentric tube heat exchanger, based on the first and second law of thermodynamics, is developed. Matlab code has been written for solving the mathematical model. The experimental set up is designed and constructed for the parameters used in the study. The mathematical model and code is validated using the experimental results. The numerical test for grid independence is also carried out. The optimum Reynolds number is found for the given geometry and working parameters.